2012
DOI: 10.1371/journal.pone.0036398
|View full text |Cite
|
Sign up to set email alerts
|

Serratamolide is a Hemolytic Factor Produced by Serratia marcescens

Abstract: Serratia marcescens is a common contaminant of contact lens cases and lenses. Hemolytic factors of S. marcescens contribute to the virulence of this opportunistic bacterial pathogen. We took advantage of an observed hyper-hemolytic phenotype of crp mutants to investigate mechanisms of hemolysis. A genetic screen revealed that swrW is necessary for the hyper-hemolysis phenotype of crp mutants. The swrW gene is required for biosynthesis of the biosurfactant serratamolide, previously shown to be a broad-spectrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 53 publications
4
51
0
Order By: Relevance
“…Previous studies demonstrated cAMP-CRP regulation of flagellum and secondary metabolite production by S. marcescens strain PIC3611 (18,21,23). Direct binding of cAMP-CRP to the promoter of the flagellar master regulator operon, flhDC, was observed, but a positive interaction between cAMP-CRP and promoters of the genes required for biosynthesis of the secondary metabolites prodigiosin (pigA-N) or serratamolide (swrW) was not (18).…”
Section: Identification Of Eepr and Eepsmentioning
confidence: 91%
See 4 more Smart Citations
“…Previous studies demonstrated cAMP-CRP regulation of flagellum and secondary metabolite production by S. marcescens strain PIC3611 (18,21,23). Direct binding of cAMP-CRP to the promoter of the flagellar master regulator operon, flhDC, was observed, but a positive interaction between cAMP-CRP and promoters of the genes required for biosynthesis of the secondary metabolites prodigiosin (pigA-N) or serratamolide (swrW) was not (18).…”
Section: Identification Of Eepr and Eepsmentioning
confidence: 91%
“…When this construct integrates, the promoter region is duplicated such that the lacZ gene becomes a reporter for eepR expression, and the native eepR gene comes under the control of the regulatory elements in the 263 bp of DNA upstream of the ORF, maintaining EepR, which may be necessary for eepR expression. For pigA and swrW promoter analysis, transcriptional lacZ fusions to internal fragments of the pigB and swrW genes (plasmids pMQ268 and pMQ223) were targeted to the chromosome by homologous recombination, verified by PCR, and used as previously described (18,21,23).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations